2013
DOI: 10.1177/1744629513509794
|View full text |Cite
|
Sign up to set email alerts
|

Raising a child with disability and dealing with life events

Abstract: Intellectual disability services recognise people with intellectual disability as a family member and aim to provide effective support that facilitates family cohesion. However, the needs of families and individuals within the family should be addressed in a holistic manner to ensure a seamless service. This article outlines a mother's reflections on her experience of raising a child with autism spectrum disorder and its impact on her life. The article focuses on one mother's feelings, coping or lack of coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
0
11
0
2
Order By: Relevance
“…Many families want to have and raise a normal child, and such families hold expectations and hopes when it comes to the future of their children. On the contrary, families with disabled children might experience dramatic changes in their social lives, family plans, lives, economic conditions, emotional states, and expectations for the future (O'Connell, O'Halloran, & Doody, 2013). Schild (1971), Fortier and Wanlass (1984), Eripek (1996), and Akkök (1997) put forth that starting from the moment when a family learns they have a disabled child, emotional and adaptive processes generally go through the following phases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many families want to have and raise a normal child, and such families hold expectations and hopes when it comes to the future of their children. On the contrary, families with disabled children might experience dramatic changes in their social lives, family plans, lives, economic conditions, emotional states, and expectations for the future (O'Connell, O'Halloran, & Doody, 2013). Schild (1971), Fortier and Wanlass (1984), Eripek (1996), and Akkök (1997) put forth that starting from the moment when a family learns they have a disabled child, emotional and adaptive processes generally go through the following phases.…”
mentioning
confidence: 99%
“…As mentioned above, mothers are the ones generally responsible for the care and education of disabled children, and they do not receive adequate support from their partners. In a study examining mothers with disabled children, they were found to often feel abandoned, lonely, and isolated from social life; they expressed a sense of disappointment, feeling that their pain went unnoticed throughout this period (O'Connell et al, 2013).…”
mentioning
confidence: 99%
“…Overall, this has been a positive journey that has resulted in four articles being submitted and accepted for publication Doody, 2013a, 2013b;O'Halloran et al, 2013;O'Connell et al, 2013). It has also been emotional at times, but for me this could not have been achieved without the support and guidance of my mentor.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, Zara's mum has written her own experience (O'Connell et al . ) and the readers can balance the overall experience through both publications.…”
Section: Discussionmentioning
confidence: 99%